2020
DOI: 10.21660/2020.72.5636
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traditional Thai Massage on Muscle Oxygen Saturation in Low Back Pain Patients: A Preliminary Study

Abstract: Low Back Pain (LBP) is a common disease found in every age that affects daily life. LBP may cause poor posture of the lumbar spine, and decrease muscle performance which leads to muscle fatigue, reduce blood circulation and reduce muscle oxygen saturation. Traditional Thai Massage (TTM) has been used to treat patients with LBP for a long time with some evidence that it could increase muscle flexibility, improve blood circulation and decrease pain. However, its effect on muscle oxygen saturation has not been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The duration of the percussive massage was 15 min. The use of this percussion frequency was based on the fact that a PT of 30 Hz is appropriate for myofascial release [25], and also that previous studies have found a 15 min duration of back massage to be beneficial [26,27]. The researcher placed the massage head vertically on the participants' backs.…”
Section: Intervention Protocolmentioning
confidence: 99%
“…The duration of the percussive massage was 15 min. The use of this percussion frequency was based on the fact that a PT of 30 Hz is appropriate for myofascial release [25], and also that previous studies have found a 15 min duration of back massage to be beneficial [26,27]. The researcher placed the massage head vertically on the participants' backs.…”
Section: Intervention Protocolmentioning
confidence: 99%
“…Several studies documented the sensitivity of oxygenation sensor used in this study. For example, Oatyimprai et al [58] found that the percentage of SmO2 immediately increased after the subject received traditional Thai massage due to the improvement in blood flow. In another study, Schlegel and Hiblbauer [59] found that the SmO2 dropped from 55% to 10% during the isometric exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulative approaches applied to the feet can contribute to the resolution of peripheral edema by increasing the blood flow to the kidney and helping the fluid-volume balance in the body 27. Other studies emphasize that therapeutic approaches such as massage are beneficial for circulation 28–30…”
Section: Discussionmentioning
confidence: 99%
“…27 Other studies emphasize that therapeutic approaches such as massage are beneficial for circulation. [28][29][30] For this reason, it is thought that foot massage can be used as a useful, easy, and side effect-free method in resolving peripheral edema, one of the most common symptoms of heart failure. Also, important information about the course of heart failure can be obtained with the evaluation during the massage application.…”
Section: The Effect Of Foot Massage On Peripheral Edemamentioning
confidence: 99%